Correction: Diketopyrrolopyrrole based organic semiconductors with different numbers of thiophene units: symmetry tuning effect on electronic devices. (22nd February 2018) - Liu, Qian; Surendran, Abhijith; Feron, Krishna; Manzhos, Sergei; Jiao, Xuechen; McNeill, Christopher R.; Bottle, Steven E.; Bell, John; Leong, Wei Lin; Sonar, Prashant
Abstract : Correction for 'Diketopyrrolopyrrole based organic semiconductors with different numbers of thiophene units: symmetry tuning effect on electronic devices' by Qian Liu et al., New J. Chem., 2018, DOI: ;10.1039/c7nj03505e .